Postgenderisme dalam Tinjauan Hukum Islam - Akhmad Wafi; Amelia Fatmawati; Almejiem Aditya Wijaya (JOURNAL OF ISLAMIC AND LAW STUDIES, 2022)
Postgenderism is an idea that seeks to eliminate gender inhumans with the help of technology. The birth of this idea is ofcourse a concern, especially in the Islamic religion. This articleexamines the position of postgenderism in the Islamic genderperspective and postgenderism in the view of maqasid sharia.Through Islamic Studies research methods, it was concluded thatpostgenderism violates the gender provisions in Islam, wherehumans are created as male and female, and is also different fromthe concept of khuntsa or double sex. Based on a review of maqasidsharia, postgenderism is contrary to the main principles in Islam,namely hifz ad-din (maintaining religion), hifz an-nafs (maintainingself/soul), and hifz an-nasl (maintaining offspring), as well ashifzul mal. This idea of postgenderism erodes faith in the verses ofthe Koran which emphasize gender differences as God's will. Inaddition, gender modification using technology has the potential tocause birth defects in babies, which is contrary to the principle ofmaintaining personal health and safety. Postgenderism aims atpersonal pleasure without considering the preservation of humansand offspring, contrary to the aim of preserving offspring andmaintaining the human population on earth.